2008
DOI: 10.1128/jvi.01003-08
|View full text |Cite
|
Sign up to set email alerts
|

Within-Host Genetic Diversity of Endemic and Emerging Parvoviruses of Dogs and Cats

Abstract: Viral emergence can result from the adaptation of endemic pathogens to new or altered host environments, a process that is strongly influenced by the underlying sequence diversity. To determine the extent and structure of intrahost genetic diversity in a recently emerged single-stranded DNA virus, we analyzed viral population structures during natural infections of animals with canine parvovirus (CPV) or its ancestor, feline panleukopenia virus (FPV). We compared infections that occurred shortly after CPV emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 48 publications
2
74
1
Order By: Relevance
“…NS2 knockout mutants in the infectious clone of CPV show no obvious differences in viral DNA replication in cell culture or in dogs (65). However, recent studies examining the within-host genetic diversity of CPV infection showed that NS2 might play a role in host adaptation of CPV (30). MVM NS2 is a multifunctional protein; it also has a role in ssDNA production, capsid assembly, and nuclear export of virions (16,24,43,45,55).…”
Section: Discussionmentioning
confidence: 99%
“…NS2 knockout mutants in the infectious clone of CPV show no obvious differences in viral DNA replication in cell culture or in dogs (65). However, recent studies examining the within-host genetic diversity of CPV infection showed that NS2 might play a role in host adaptation of CPV (30). MVM NS2 is a multifunctional protein; it also has a role in ssDNA production, capsid assembly, and nuclear export of virions (16,24,43,45,55).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evolutionary mechanisms that allow this virus to infect new hosts and the emergence of new strains in "real time" are complex and not yet understood. 15 The new variants of CPV appear to be able to infect cats and other hosts (puma, coyote, gray wolf, bobcat, raccoon, and striped skink) because the variants can bind the feline transferrin receptor as well as the receptors of other hosts, 1,16 while still remaining a severe threat to dogs. The role of these variants in cats still remains somewhat uncertain.…”
Section: Research-article2014mentioning
confidence: 99%
“…For instance, parvoviruses experienced adaptive evolution of the gene encoding the surface-exposed viral protein, the capsid, after this virus first became established in dogs in the 1970s (Hoelzer et al, 2008). These evolutionary changes improved the interaction between the capsid and the dog-encoded cell-surface receptor for virus entry, the transferrin receptor.…”
Section: Signatures Of Positive Selection In Ranavirus Genomesmentioning
confidence: 99%
“…Computational tools that can detect episodes of rapid adaptation of specific genes, in conjunction with the increased availability of genomic data, have provided new avenues for identifying candidate genes potentially involved in dynamic processes such as host switching (Sawyer & Elde, 2012). In many cases, genes that are involved in host-pathogen interactions exhibit episodes of intense positive selection during the process of establishing a new host species (Shackelton et al, 2005;Hoelzer et al, 2008;Meyerson & Sawyer, 2011;Bhatt et al, 2013). Genes identified via these methods are often involved in immune evasion, replication, reproduction, gene expression, host-pathogen co-evolution and host defences (Endo et al, 1996;Yang et al, 2000;McLysaght et al, 2003;Harrison & Bonning, 2004;Shackelton et al, 2005;Sabeti et al, 2006;Kosiol et al, 2008;Elde et al, 2012).…”
Section: Introductionmentioning
confidence: 99%